Growth Response Of SRI Rice In Suboptimal Land To Application Of Cattle Manure And Kieserite - Nalwida Rozen; Musliar Kasim; Agustian Agustian; Indra Dwipa (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
Population growth rates cause an increase in food demand, but the planting area is decreasing due to land-use change. The land available to be utilized by farmers is mostly suboptimal land. The disadvantages of suboptimal land are low pH values ​​(4.7) and a small number of nutrients (Nitrogen = 0.11%, Phosphorus = 0.45 ppm, very low Carbon, very high Aluminum, and medium Cation exchange capacity) and for increasing the value of suboptimal land can be given organic fertilizer such as cattle manure and kieserite. This study aims to determine the effect of cattle manure and kieserite on rice growth with the SRI planting system in suboptimal land. The study was carried out in farmers' paddy fields at Ambacang Market, Kuranji District, Padang from June to October 2019. This experiment uses a completely randomized design (CRD). Data were analyzed by the F test at a 5% significance level. If it is significantly different, it is continued with the Honestly Significant Difference test (HSD) at the 5% significance level. The results showed that the application of cattle manure and kieserite can increase the height of rice plants and the number of tillers.